Transendothelial movement of adiponectin is restricted by glucocorticoids. Issue 2 (August 2017) - Dang, Thanh Q; Yoon, Nanyoung; Chasiotis, Helen; Dunford, Emily C; Feng, Qilong; He, Pingnian; Riddell, Michael C; Kelly, Scott P; Sweeney, Gary
Abstract : Altered permeability of the endothelial barrier in a variety of tissues has implications both in disease pathogenesis and treatment. Glucocorticoids are potent mediators of endothelial permeability, and this forms the basis for their heavily prescribed use as medications to treat ocular disease. However, the effect of glucocorticoids on endothelial barriers elsewhere in the body is less well studied. Here, we investigated glucocorticoid-mediated changes in endothelial flux of Adiponectin (Ad), a hormone with a critical role in diabetes. First, we used monolayers of endothelial cells in vitro and found that the glucocorticoid dexamethasone increased transendothelial electrical resistance and reduced permeability of polyethylene glycol (PEG, molecular weight 4000 Da). Dexamethasone reduced flux of Ad from the apical to basolateral side, measured both by ELISA and Western blotting. We then examined a diabetic rat model induced by treatment with exogenous corticosterone, which was characterized by glucose intolerance and hyperinsulinemia. There was no change in circulating Ad but less Ad protein in skeletal muscle homogenates, despite slightly higher mRNA levels, in diabetic vs control muscles. Dexamethasone-induced changes in Ad flux across endothelial monolayers were associated with alterations in the abundance of select claudin tight junction (TJ) proteins. shRNA-mediated knockdown of one such gene, claudin-7, in HUVEC resulted in decreased TEER and increased adiponectin flux, confirming the functional significance of Dex-induced changes in its expression. In conclusion, our study identifies glucocorticoid-mediated reductions in flux of Ad across endothelial monolayers in vivo and in vitro . This suggests that impaired Ad action in target tissues, as a consequence of reduced transendothelial flux, may contribute to the glucocorticoid-induced diabetic phenotype.